The Implementation of Islamic Education Teaching Methods in Ni'matul Habib's Perspective in the Modern Era - Akbar Aisya Billah; Basuki Basuki (At-Ta'lim : Media Informasi Pendidikan Islam, 2023)
Abstract: Implementation of Islamic Education Teaching Methods According to Ni'matul Habib's Perspective in the Modern EraTeaching methods are the art of teaching so that the material will be conveyed well to students if the right teaching methods are used. In this modern era, Islamic religious knowledge and humans are experiencing very rapid dynamism, where Islamic education will apply throughout the ages. So that by studying the sources of Islamic education in full and with a good understanding, humans can face the challenges of changing times, especially in the world of education. This research aims to describe and analyze the teaching methods of Islamic education according to Ni’matul Habib and its implementation in this modern era by looking at various development phenomena in the world of education. This research uses literature study with the main source being the book Thara'iqu Tadrisi-t-Tarbiyah Al-Islamiyyah by Ni'matul Habib. This research produces a description and application of Islamic education-based teaching methods in the modern era which include: (1) Discussion method (2) Inductive method (3) Deductive method (4) Problem-solving method (5) Cooperative method (6) Storytelling method.Abstrak: Implementasi Metode Pengajaran Pendidikan Agama Islam menurut Perspektif Ni'matul Habib di Era Modern Metode pengajaran merupakan seni dalam mengajar, sehingga materi akan tersampaikan dengan baik kepada peserta didik jika menggunakan metode pengajaran yang tepat. Di era modern ini, ilmu agama Islam dan manusia mengalami dinamisme yang sangat cepat, dimana pendidikan Islam akan berlaku di sepanjang zaman. Sehingga dengan mempelajari sumber-sumber pendidikan Islam yang utuh dan dengan pemahaman yang baik, manusia dapat menghadapi tantangan perubahan zaman terutama didalam dunia pendidikan. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis metode pengajaran pendidikan Islam menurut Ni’matul Habib dan implementasinya di era modern dengan melihat berbagai fenomena perkembangan di dalam dunia pendidikan. Penelitian ini menggunakan studi kepustakaan dengan sumber utama buku Thara’iqu Tadrisi-t-Tarbiyah Al-Islamiyyah karya Ni’matul Habib. Penelitian ini menghasilkan deskripsi dan penerapan metode pengajaran berbasis pendidikan Islam di era modern yang meliputi: (1) Metode diskusi (2) Metode induktif (Inductive method) (3) Metode deduktif (Deductive method) (4) Metode pemecahan masalah (Problem solving) (5) Metode kooperatif (6) Metode bercerita.